The context in which teachers exercise agency and autonomy in directing and completing their own research: a teacher-led, academic-facilitated research group. (6th November 2020) - Podesta, Ed; Hoath, Leigh
ABSTRACT: This paper explores the contexts of the decision-making of seven Teacher Researchers in an informal practitioner research group which we facilitated. The group was established to support teachers in undertaking small-scale professional research studies within their own settings. This paper focuses on the contexts of the decisions about research questions undertaken by the teachers, each of which were given one stipulation of working to the demands of educational research ethics throughout their study, in the hope that teachers would therefore be able to exercise high levels of agency in making these decisions. Although agency is often perceived as something individual teachers possess, we suggest that this conception of agency is limited. Data collection took the form of a focus group which was analysed through a coding approach to identify emerging themes. Focus group interviews were thematically coded. We found that teachers' decision-making about practitioner research is heavily framed by their contexts and their professional histories, as well as the access to time and resource to carry out research that is afforded to them. However, even within these constraints, they are active agents, who have embraced the tools of accountability rather than submitted to them.